PENERAPAN STUDI REKAYASA NILAI PADA PERENCANAAN STRUKTUR ATAP GEDUNG SERBA GUNA UNIVERSITAS MUHAMMADIYAH MALANG - Retno, Dyah; Hastuti, Hermy Dyah (Department Industrial Engineering, University of Muhammadiyah Malang, 2002)
This research will apply value engineering study in planing roof Astructure of UMM's Multi Function Building (GSG). The planing includes roof geometry and material used as roofcover and skeletons. Steps taken includes information stage that have goal in determining criteria necessary in planing the roof structure and weight of the criteria,creativity stage in which we will develop roof structure altematives as many as possible by using FAST diagram,and then evaluation stage in which we will make assessment on those altematives by using feasibility and evaluation matrix, performance calculation,and calculation of cost required by respective altematives.In development st age we will make value calculation of respective alternatives, inwhich an altemative with the highest value will be chosen as proposal for roof of UMM's Multi Function Building.